Model of 9Be nucleus as "quasi-molecular" state of “n+a+a” system (Physical Sciences and Technology, 2015)
The 9Be nuclide has been considered as a system of two alpha-particles and one neutron and it has been shown that such system can exist in "quasi-molecular" state, when the wave number of a pair of heavy particles becomes imaginary with the wave number of the light particle being a real quantity. That is, rescattering of light particles on the two heavy particles creates additional attraction between the heavy particles and "binds" this heavy pair. The total energy of the system becomes negative: , m is the mass of the light particle, and M is the mass of the heavy particle. Since , the total energy of the system has a minimum for the variable . The estimates were obtained in the Born-Oppenheimer approximation, where the choice of the pair potentials in separable form allows to solve the three body problem in a simple and compact form.
Keywords: beryllium 9; nuclear models; quasi-molecular state; Born-Oppenheimer approximation; three body problem.